Synthesis and Coordination Behavior of a Flexible Bis(phosphinoferrocene) Ligand - Schulz, Jiří; Leitner, Zdeněk; Císařová, Ivana; Štěpnička, Petr (Molecules (Basel, Switzerland), 2018)
A symmetrical flexible bis(phosphinoferrocene) derivative, viz. bis[1'-(diphenylphosphino)ferrocenyl]methane (1), was prepared and studied as a ligand in Pd(II) and Au(I) complexes. The reactions of 1 with [PdCl₂(cod)] (cod = cycloocta-1,5-diene) and [Pd(μ-Cl)(LNC)]₂ (LNC = [2-(dimethylamino-κN)methyl]phenyl-κC¹) produced bis(phosphine) complex trans-[PdCl₂(1-κ²P,P')] (4), wherein the ligand spans trans positions in the square-planar coordination sphere of Pd(II) and the tetranuclear, P,P-bridged complex [(μ(P,P')-1){PdCl(LNC)}₂] (5), respectively. In reactions with the Au(I) precursors [AuCl(tht)] and [Au(tht)₂][SbF₆] (tht = tetrahydrothiophene), ligand 1 gave rise to tetranuclear Au₂Fe₂ complex [(μ(P,P')-1)(AuCl)₂] (6) and to symmetrical macrocyclic tetramer [Au₄(μ(P,P')-1)₄][SbF₆]₄ (7). All compounds were characterized by spectroscopic methods. In addition, the structures of compound 1, its synthetic precursor bis[1'-(diphenylphosphino)ferrocenyl]methanone (3), and all aforementioned Pd(II) and Au(I) complexes were determined by single-crystal X-ray diffraction analysis (some in solvated form).
Keywords: structure elucidation; gold; Metallocenes; železo; zlato; fosfiny; Molecular Structure; Phosphines; komplexní sloučeniny; ferrocene ligands; krystalografie rentgenová; Ligands; Coordination Complexes; palladium; metaloceny; molekulární struktura; Iron; phosphines; Gold; Crystallography, X-Ray; Palladium; ligandy